First record of Rhaphidosoma atkinsoni (Heteroptera: Reduviidae: Harpactorinae) from Maharashtra, India, with redescription and observations on its bionomics - Pansare, Pratik P.; Joshi, Nikhil U.; Boyane, Swapnil S.; Ghate, Hemant V. (Zootaxa, 2017)
A relatively less known assassin bug, Rhaphidosoma atkinsoni Bergroth, 1893 (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) is recorded from Maharashtra State, India, for the first time. Redescription and illustrations of the species, along with the notes on morphology and natural history, are provided.